جرائم الصفقات العمومية على ضوء التشريعات المتعلقة بالوقاية من الفساد ومكافحته - ناصف, عبلة (University of Eloued جامعة الوادي, 2022)
تعد الجزائر أحد الدول التي تسعى جاهدة لخلق توازنات اقتصادية الهدف منها النهوض بالدولة والمضي بها قدماّ، ولعل انتشار الجرائم الاقتصادية يعتبر أحد النتائج المنبثقة على ذلك، لذا عكفت الدولة على صياغة منظومة تشريعية تسعى منها خلالها لمكافحة الفساد في شتى مجالاته لاسيما في مجال الصفقات العمومية، فصدر بذلك القانون 06-01 المؤرخ في 2006 المتضمن الوقاية من الفساد ومكافحته لينظم مسألة القواعد الإجرائية والعقوبات المقررة لكل جريمة من جرائم الصفقات العمومية. Abstract : Algeria is considered as one of the major countries tries to create an "economic balances" in order to advance the state and moving it forward, besides, the spread of economic crimes is one of the results behind economic growth where the country worked to formulate a legislative system able to combat corruption in various fields escpecially "DEALS", therefore, the law 06-01 was issued related to the prevention and control of corruption and to put down procedural and penalites rules prescribed for each crime related to "DEALS"
Public procurement crimes in the light of related legislation to the preventi on and control of corruption
مقال
Keywords: الجرائم ،الصفقات العمومية ، المحاباة ، الامتيازات،العقوبات; penalties; Crimes, pubilc DEALS, favoritism, privileges